Determinants of Purchasing Decision of Islamic Banking Mortgages Subsidised Among Urban Millennials in Indonesia - Dahlan, Rahmat; Saadah, Nabila Lestari (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
The potential of the homeownership credit market among millennials in Indonesia is quite significant, reaching 44% of those who do not own a house. Alternative Sharia subsidised homeownership programs get affordable prices, but the market share of Sharia Bank mortgages is relatively tiny. The study aims to analyse the determining factors for millennial customers to get subsidised Islamic banking mortgages in urban areas. The research was a mixed method with an exploratory sequential design approach. The informant and respondent were domiciled in South Tangerang City, Banten Province of Indonesia. The sampling technique used snowball sampling as informants and purposive sampling with the Lemeshow formula as respondents. Data was collected through interviews with five informants from property developers, academicians, customers and managers of Bank Syariah Indonesia Griya division, questionnaires of 100 respondents as customers of Bank Syariah Indonesia, and literature studies. Descriptive thematic qualitative analysis data used triangulation techniques by Miles and Huberman, while quantitative data used regression and correlation analysis with SPSS technique. The promotional research results were carried out together, determining prices according to economic fluctuations and Bank Syariah Indonesia's brand image with accredited property developers. Multiple regression tests analysed the data. The results of the study show that the Bank Syariah Indonesia brand image is the primary determinant, and the house price is the second determinant of the credit decision of subsidised Griya Bank Syariah Indonesia home ownership. Meanwhile, in Bank Syariah Indonesia's brand image, customers who have home ownership credit are the first to consider a financing institution. Then, the price becomes a factor of consideration, along with special or limited offers, according to the customer's financial ability. The research implies that the better the Bank Syariah Indonesia brand image and house prices are, the more the customer's decision to own an urban millennial subsidised home with Bank Syariah Indonesia Griya will increase.